Indonesian Muslim society's reception of sensation language and invitation to polygamy on social media - Astari, Rika; Perawironegoro, Djamaluddin; Faturrahman, Muhammad Irfan; Kistoro, Hanif Cahyo Adi (IAIN Salatiga, 2023)
Fun Polygamy Chanel is one of the media used by Ustad Awan (UA) to socializethe call for polygamy. The language used on this polygamous YouTube usessensational language. This research aims to map the form of reception, the factorsbehind it, and its impact on public discourse on polygamy law. This qualitativeresearch uses interpretative analysis techniques starting from restatement of thedata followed by description, ending with data interpretation. The results ofthe research show that calls for polygamy using sensational language increasepublic rejection of polygamy. This public reception is influenced by personal,interpersonal expressions discussed on social media and represented in generalentertainment media (soap operas and feature films). The different receptionsthat were discussed then became a hybrid reception that increasingly dramatizedpolygamy law to the point that it was not following Islamic law.